2017
DOI: 10.33736/ijbs.491.2017
|View full text |Cite
|
Sign up to set email alerts
|

Politically Connected Banks: Some Indonesian Evidence

Abstract: We investigate the impact of being politically connected on bank performance and cost of funding. We study 89 Indonesian banks over the 2001-2008 period disentangled into politically connected banks which can be state-owned banks and private banks as well as non-politically connected banks. Controlling for bank fundamental factors and time effect, we do find that political connections improve bank performance. Moreover, our results provide evidence that politically connected banks are benefited by getting a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 32 publications
4
12
0
6
Order By: Relevance
“…Looking at the evidence above, NPL is considered salient. This also supports the previous studies such as those by Yaqinah (2020), Sutopo et al (2017), Iramani et al (2018), andGhalib (2018). They found that NPL is an important factor to increase the bank's performance that is ROA.…”
Section: Relationship Between Variablessupporting
confidence: 92%
See 1 more Smart Citation
“…Looking at the evidence above, NPL is considered salient. This also supports the previous studies such as those by Yaqinah (2020), Sutopo et al (2017), Iramani et al (2018), andGhalib (2018). They found that NPL is an important factor to increase the bank's performance that is ROA.…”
Section: Relationship Between Variablessupporting
confidence: 92%
“…There have been some studies on GCG so far, but few are related to the banking sector. Sutopo et al (2017) used corruption and political aspect towards BPD performance. Yet, the total deposit is also influential.…”
Section: Framework Of the Studymentioning
confidence: 99%
“…However, the effect may be significant for foreign firms. It is in line with the previous study of Sutopo, Trinugroho, & Damayanti (2017) in which the effect of political connections on bank performance is more pronounced for foreign-controlled banks.…”
Section: Publicness Ownership and Firm Performancesupporting
confidence: 92%
“…Besides, this study focuses on SOEs and all sectors by controlling the industrial sector and SOEs. SOE banks' profitability is higher than the profitability of non-SOEs (Sutopo, Trinugroho, and Damayanti, 2017). Meanwhile, there is no difference between SOEs'SOEs' profitability and non-SOEs'non-SOEs' profitability when comparisons were made for all industrial sectors (Ardila, Saputra, Adiati, and Sutopo, 2018), and the differences or similarities between the two types of business entities can depend on the industry (Singh, 2019).…”
Section: Debt Financing and Profitabilitymentioning
confidence: 98%